Insipidary syndrome in children and adolescents (part 1) - V. V. Smirnov; L. I. Bikbaeva (Лечащий Врач, 2021)
The review article presents current data on water-electrolyte balance in healthy and pathological state. The diseases and conditions which occur in insipidary syndrome are described. The features of the clinical picture, diagnostic methods and treatment principles are considered.